Successful versus unsuccessful antegrade recanalization of single chronic coronary occlusion: Eight‐year experience and outcomes by a propensity score ascertainment. Issue 2 (24th March 2015) - Jaguszewski, Milosz; Ciecwierz, Dariusz; Gilis‐Malinowska, Natasza; Fijalkowski, Marcin; Targonski, Radoslaw; Masiewicz, Emilia; Strozyk, Aneta; Duda, Maciej; Chmielecki, Michal; Lewicki, Lukasz; Dubaniewicz, Witold; Burakowski, Slawomir; et al.
<x xml:space="preserve">Abstract</x> Aims The effectiveness of revascularization of chronic total occlusion (CTO) remains intriguing. Thus, we sought to investigate whether a successful PCI for single CTO improves outcomes in a setting of stable angina and chronic occlusion of single coronary artery. Methods and Results Of 11 957 consecutive patients referred for nonurgent PCI between 2003 and 2010, 1110 displayed single CTO and were enrolled to the central CTO‐registry database. The primary end‐point included all‐cause mortality, the secondary end‐point a composite of safety outcome measure of all‐cause death, nonfatal‐MI, the need for urgent revascularization and stroke. The major adverse cardiovascular event (MACE) records were extracted from the national administrative database and all patients were linked to the long‐term follow‐up. Since the patient assignment was not random, we performed the propensity scoring to minimize selection bias; 734 patients (66%) had a successful PCI‐CTO. Compared with successful procedures, unsuccessful procedures had similar rates of all‐cause death both in crude (HR, 0.78; 95%CI, 0.49–1.25; P = 0.30) and adjusted analysis (HR, 0.80; 95%CI, 0.50‐1.28; P = 0.34). A similar, significant reduction in overall MACE was noted with successful PCI‐CTO compared with unsuccessful procedure in unadjusted (HR, 0.74; 95%CI, 0.56–0.96; P = 0.020) and adjusted calculation (HR, 0.73; 95%CI, 0.56–0.96; P = 0.019). Patients after successful PCI‐CTO as compared with failed recanalization less frequently underwent surgical revascularization. The benefit was sustained at 3 years follow‐up. Conclusions Successful PCI for single CTO does not improve long‐term survival, nonetheless, is associated with reduced overall MACE and the need for surgical revascularization. © 2015 Wiley Periodicals, Inc.